In Silico Assessment of ADME Properties: Advances in Caco-2 Cell Monolayer Permeability Modeling - Pham-The, Hai; Cabrera-Pérez, Miguel Á.; Nam, Nguyen-Hai; Castillo-Garit, Juan A.; Rasulev, Bakhtiyor; Le-Thi-Thu, Huong; Casañola-Martin, Gerardo M. (Current Topics in Medicinal Chemistry, 2018)
One of the main goals of in silico Caco-2 cell permeability models is to identify those drug substances with high intestinal absorption in human (HIA). For more than a decade, several in silico Caco-2 models have been made, applying a wide range of modeling techniques; nevertheless, their capacity for intestinal absorption extrapolation is still doubtful. There are three main problems related to the modest capacity of obtained models, including the existence of inter- and/or intra-laboratory variability of recollected data, the influence of the metabolism mechanism, and the inconsistent in vitro-in vivo correlation (IVIVC) of Caco-2 cell permeability. This review paper intends to sum up the recent advances and limitations of current modeling approaches, and revealed some possible solutions to improve the applicability of in silico Caco-2 permeability models for absorption property profiling, taking into account the above-mentioned issues.
Keywords: Human intestinal absorption